2018
DOI: 10.1038/s41390-018-0149-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D receptor gene FokI polymorphism and susceptibility to CAP in Egyptian children: a multicenter study

Abstract: The VDR gene Fok I (rs2228570) polymorphism confers susceptibility to CAP in Egyptian children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
3
6
0
Order By: Relevance
“…In an attempt to explain our findings, we investigated the 25(OH) D serum level in relation to the studied VDR polymorphism, which was found to be significantly lower in patients homozygous for the Fok I FF genotype compared to those carrying the ff and Ff genotypes. These results are concordant with a recent multicenter study by Abouzeid et al 42 who investigated the VDR Fok I polymorphism on genomic DNAs of 300 children diagnosed with communityacquired pneumonia. The authors reported that the VDR Fok I FF genotype was associated with lower serum 25(OH) D levels and may confer susceptibility to CAP and related hospital mortality in the under-five Egyptian children.…”
Section: Discussionsupporting
confidence: 92%
“…In an attempt to explain our findings, we investigated the 25(OH) D serum level in relation to the studied VDR polymorphism, which was found to be significantly lower in patients homozygous for the Fok I FF genotype compared to those carrying the ff and Ff genotypes. These results are concordant with a recent multicenter study by Abouzeid et al 42 who investigated the VDR Fok I polymorphism on genomic DNAs of 300 children diagnosed with communityacquired pneumonia. The authors reported that the VDR Fok I FF genotype was associated with lower serum 25(OH) D levels and may confer susceptibility to CAP and related hospital mortality in the under-five Egyptian children.…”
Section: Discussionsupporting
confidence: 92%
“…According to a study conducted in Saudi children having acute lower respiratory tract infection (ALRTI), neither vitamin D status nor VDR gene polymorphisms such as ApaI or TaqI were associated with higher susceptibility to ALRTI [31]. However, according to a study on community-acquired pneumonia in Egyptian children, the VDR gene FokI polymorphism confers susceptibility to community-acquired pneumonia in Egyptian children [32]. A similar observation was made in children from India [33].…”
Section: Discussionmentioning
confidence: 87%
“…VDR SNPs have been associated with severe RSV bronchiolitis and vitamin D pathway has been related to the severity of SARS-CoV-2 infection 15 , 23 . TaqI has been previously linked to susceptibility to lower respiratory tract infections in early childhood and to tuberculosis in adults 16 , 24 . Furthermore, VDR SNPs have been associated with community acquired pneumonia in children and with S. aureus nasal carriage in patients with type I diabetes 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%